Trendjacking Strategies by Influences : Their Impact on Engagement and Costumer Purchase Decisions in the Digital Era - Heti Hendrayati; Irma Setyawati; Tri Waluyo (MultiTech Publisher, 2024)
This research aims to understand the impact of trendjacking strategies employed by influencers on audience engagement and consumer purchase decisions in the digital era. We used a quantitative research approach to collect data from respondents and analyze the relationship between engagement, influencer influence, and purchase decisions. The study shows that high engagement positively correlates with purchase decisions, with 70% of actively engaged respondents more likely to buy products promoted by influencers. Furthermore, influencers not only directly influence purchase decisions but also enhance audience engagement with the content they present. This study highlights the importance of authenticity and content relevance in marketing strategies and the use of trendjacking as a method to increase brand awareness and effectively influence consumer behavior. These findings provide valuable insights for marketers in designing more effective campaigns on social media platforms.